2019
DOI: 10.18632/aging.102543
|View full text |Cite
|
Sign up to set email alerts
|

Reduced miR-203 predicts metastasis and poor survival in esophageal carcinoma

Abstract: We analyzed data from two non-coding RNA profiling arrays made available by the Gene Expression Omnibus (GEO) and found 17 miRNAs with remarkable differential expression between malignant and normal esophageal tissue. Correlation analysis between expression of these 17 miRNAs and patients' clinicopathological characteristics showed that miR-203 was down-regulated in esophageal carcinoma (EC) tissues and was significantly associated with lymph node metastasis and poor overall survival. Overexpression of miR-203… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The goal of our re-analysis was to exclusively represent relative expression of miR-203 in EC tissue and tumor-adjacent normal tissue. Confirming the previous findings [ 24 ], in 119 paired patient samples in GSE43732, miR-203 expression was significantly downregulated in esophageal tumor tissue (Fig. 1 c; P < 0.0001) and in 104 tumor-adjacent normal tissue and 153 esophageal tumor tissue patient samples in GSE6188, miR-203 expression was significantly downregulated in esophageal tumor tissue (Fig.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The goal of our re-analysis was to exclusively represent relative expression of miR-203 in EC tissue and tumor-adjacent normal tissue. Confirming the previous findings [ 24 ], in 119 paired patient samples in GSE43732, miR-203 expression was significantly downregulated in esophageal tumor tissue (Fig. 1 c; P < 0.0001) and in 104 tumor-adjacent normal tissue and 153 esophageal tumor tissue patient samples in GSE6188, miR-203 expression was significantly downregulated in esophageal tumor tissue (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Obviously, USP26 is not the only target of miR-203a-5p. In the context of EC, miR-203a's function has been to inhibit β-catenin signaling, cell migration and invasion via directly inhibiting KIF5C expression in turn potentiating the antitumor activities of the downstream protein, Axin2 [24]. Different targets of miR-203a have been defined in the context of other cancers, like RAB22A (encoding Rasrelated protein Rab-22A) and BIRC5 (encoding survivin) in osteosarcoma [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-203 is one of the important members of the miRNAs family, and located on human chromosome 14 q32, 33-site (17). Studies have shown that miR-203 is abnormally expressed in a variety of tumor tissues including esophageal carcinoma (down-regulation), osteosarcoma (down-regulation), ovarian cancer (upregulation), and prostate cancer (down-regulation), and is closely related to tumor cell growth, metastasis and invasion (18)(19)(20)(21)(22)(23). A recent study reported that miRNA-203 restrains epithelial-mesenchymal transition, invasion and migration of papillary thyroid cancer via downregulating AKT3 expression (24).…”
Section: Introductionmentioning
confidence: 99%